Risk factors for bleeding hepatocellular adenoma in a United States cohort. (12th November 2021) - McDermott, Chelsea; Ertreo, Marco; Jha, Reena; Ko, Jimin; Fernandez, Stephen; Desale, Sameer; Fishbein, Thomas; Satoskar, Rohit; Winslow, Emily; Smith, Coleman; Hsu, Christine C
Abstract: Background & Aims: Known risk factors for hepatocellular adenoma (HCA) bleeding are size >5 cm, growth rate, visible vascularity, exophytic lesions, β‐catenin and Sonic Hedgehog activated HCAs. Most studies are based on European cohorts. The objective of this study is to identify additional risk factors for HCA bleeding in a US cohort. Methods: Retrospective chart review was performed on patients diagnosed with HCA on magnetic resonance imaging (n = 184) at an academic tertiary institution. Clinical, pathological, and imaging data were collected. Primary outcomes measured were HCA bleeding and malignancy. Statistical analysis was performed with SAS 9.4 using Chi‐Square, Fisher's exact test, sample t test, non‐parametric Wilcoxon test, and logistic regression. Results: After excluding patients whose pathology showed focal nodular hyperplasia and non‐adenoma lesions, follow‐up data were available for 167 patients. 16% experienced microscopic or macroscopic bleeding and 1.2% had malignancy. HCA size predicted bleeding ( P < .0001) and no patients with lesion size <1.8 cm bled. In unadjusted analysis, hepatic adenomatosis (≥10 lesions) trended towards 2.8‐fold increased risk of bleeding. Of patients with a single lesion that bled, 77% bled from a lesion >5 cm. In patients with multiple HCAs that bled, 50% bled from lesions <5 cm. In patients with multiple adenomas, size ( P = .001) independently predicted bleeding and hepatic steatosis trended towards increased risk of bleeding ( P = .05). Conclusions: In a large US cohort, size predicted increased risk of HCA bleeding while hepatic adenomatosis trended towards increased risk of bleeding. In patients with multiple HCAs, size predicted bleeding and hepatic steatosis trended toward increased risk of bleeding.